2022
DOI: 10.1021/acs.biomac.2c00169
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence-Shadowing Nanoparticle Clusters for Real-Time Monitoring of Tumor Progression

Abstract: Monitoring tumor progression is important for elucidating appropriate therapeutic strategies in response to anticancer therapeutics. To fluorescently monitor the in vivo levels of tumor-specific enzymes, we prepared matrix metalloprotease (MMP)-responsive gold nanoparticle (AuNP) clusters to sense tumor microenvironments. Specifically, AuNPs and quantum dots (QDs) were surface-engineered with two poly(ethylene glycol)[PEG] shells and cyclooctyne moieties, respectively, for the copper-free click reaction. Upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…A to D adapted with permission from ref. [87] Copyright 2022 American Chemical Society. (E) Schematic principle of a QD-AuNP NSET aptasensor for AMP quantification.…”
Section: Plasmon-quenched Fluorescence (Pqf) In Metal-qd Nanohybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…A to D adapted with permission from ref. [87] Copyright 2022 American Chemical Society. (E) Schematic principle of a QD-AuNP NSET aptasensor for AMP quantification.…”
Section: Plasmon-quenched Fluorescence (Pqf) In Metal-qd Nanohybridsmentioning
confidence: 99%
“…In one recent study, Yoo et al developed a rather unconventional NSET strategy, which employed target-specific in vitro and in vivo click chemistry for switching QD PL. 87 The NSET system consisted of AuNPs (diameter ∼27 nm) as acceptors and CdSSe/ZnS QDs ( λ em ∼ 520 nm) as donors (Fig. 6A).…”
Section: Plasmon-quenched Fluorescence (Pqf) In Metal–qd Nanohybridsmentioning
confidence: 99%
“…Previous studies confirmed that AuNPs have a specific plasmon absorbance at approximately 520 nm; this peak can be red-shifted due to the increase in size by PEGylation, and the degree of PEGylation and the length of the decorated PEG can influence the red shift. 23,30 Although the FE-TEM images revealed a smaller particle size due to the collapsed PEG chains, combining the hydrodynamic size and spectroscopic results, it is clear that bare AuNPs were surface-engineered with double layers of PEG shells. 23…”
Section: Resultsmentioning
confidence: 99%
“…23,30 Although the FE-TEM images revealed a smaller particle size due to the collapsed PEG chains, combining the hydrodynamic size and spectroscopic results, it is clear that bare AuNPs were surface-engineered with double layers of PEG shells. 23…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation